Penguatan Hasil Belajar Peserta Didik Terhadap Assesmen Dengan Memanfaatkan Paradigma Baru - Anjarwati, Ani; Az-Zahra, Putri Fatimattus; Putri, Dita Refani; Kunanti, Rr Ghina Ayu Putri Tya; Diana, Dewi Rafika Nur (Jurnal Pendidikan, Sains Dan Teknologi, 2022)
In the 21st century learning period requires educators to be more skilled in processing learning media as creatively as possible by utilizing current technological developments. Utilization of this technology can be used as a solution to improve student learning outcomes in understanding HOTS assessment. This research was conducted at Kedungdalem 2 Public Elementary School Class 5 by focusing on the material "Human Circulatory System" which was considered difficult for students to understand. In its implementation, the researchers utilized a 4D application-based learning media, namely "DEVAR" as a learning medium with PjBL and Scientific learning models. The method in research is Classroom Action Research which is a controlled investigative process to find and solve learning problems in the classroom. The results obtained in conducting classroom action research using the "DEVAR" application were carried out well by the researchers, so that the initial pre-test increased by 26.93% and the post-test increased to 42.30%.